Psychological factors mediate key symptoms of fibromyalgia through their influence on stress. Issue 9 (September 2016) - Malin, Katrina; Littlejohn, Geoffrey
Abstract The clinical features of fibromyalgia are associated with various psychological factors, including stress. We examined the hypothesis that the path that psychological factors follow in influencing fibromyalgia symptoms is through their direct effect on stress. Ninety-eight females with ACR 1990 classified fibromyalgia completed the following questionnaires: The Big 5 Personality Inventory, Fibromyalgia Impact Questionnaire, Perceived Stress Scale, Profile of Mood States, Mastery Scale, and Perceived Control of Internal States Scale. SPSS (PASW version 22) was used to perform basict tests, means, and standard deviations to show difference between symptom characteristics. Pathway analysis using structural equation modelling (Laavan) examined the effect of stress on the relationships between psychological factors and the elements that define the fibromyalgia phenotype. The preferred model showed that the identified path clearly linked the psychological variables of anxiety, neuroticism and mastery, but not internal control, to the three key elements of fibromyalgia, namely pain, fatigue and sleep (p  < 0.001), via the person's perceived stress. Confusion, however, did not fit the preferred model. This study confirms that stress is a necessary link in the pathway between certain identified, established and significant psychological factors and key fibromyalgia symptoms. This has implications for the understanding of contributing mechanisms and the clinical care of patients with fibromyalgia.